Desenvolvimento de filmes à base de carrageanas das algas marinhas Solieria filiformis e Hypnea murciformis e de um alginato comercial - Paula, Gabriela Almeida de (2013)
It’s growing up the search for the development of biodegradable packages, because most oh the used nowadays are derived from petroleum and from synthetic materials which leads to a growth on the ambiental polution level. One proposal would be the use of natural biopolymers, such as the polysaccharides, proteins and lipids, as they are materials capable of forming a continuous and cohesive matrix, besides being biodegradable, renewable and abundant in nature. The main objective of the study was to develop eatable films based on carrageenan type iota and kappa extracted from seaweed Solieria filiformis and Hypnea musciformes, respectively and commercial alginate and evaluating the rheological properties of the filmogenic solutions of those movies. Ten were obtained by treatment of a mixture delineation (centroid simplex) to evaluate the effect of the proportions between the three components iota-carrageenan (0 - 100% w / w), kappa-carrageenan (0 - 100% w / w) and alginate (0 - 100% w / w) on the properties of the formed films. The rheological analysis properties of the filmogenic solutions were determined by measurements oscillatory and non-oscillatory schemes. The characterization of the films was performed by the following analyzes: mechanical properties (tensile strength, elongation at break, elastic modulus), opacity and permeability to water vapor (PWV). The water vapor permeability of the films produced was significantly (p <0.05) increased by kappa-carrageenan. The tensile strength and elastic modulus showed maximum value in an intermediate range of concentration of kappa-carrageenan and alginate. The contact angle measurement showed that the films produced are highly hydrophilic. The results of the rheological properties of the filmogenic solutions, the blends of kappa-carrageenan, iota-carrageenan and alginate presented a pseudoplastic. The concetration between the carrageenan and alginate greatly influenced the thinning of the solutions.